2004
DOI: 10.2134/jeq2004.9900
|View full text |Cite
|
Sign up to set email alerts
|

Soil Variables for Predicting Potential Phosphorus Release in Swedish Noncalcareous Soils

Abstract: The accumulation of P in agricultural soils due to fertilization has increased the risk of P losses from agricultural fields to surface waters. In risk assessment systems for P losses, both P release from soil to solution and transport mechanisms need to be considered. In this study, the overall objective was to identify soil variables for prediction of potential P release from soil to solution. Soils from nine sites of the Swedish long-term fertility experiment were used, each with four soil P levels. Phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 40 publications
6
47
0
1
Order By: Relevance
“…Only 20 % of this was in an ALextractable form (and hence reactive in short-term laboratory experiments). This result can be compared to the study of Börling et al (2004), who reported results for Kungsängen and for eight other Swedish soil fertility experiments with similar P fertilization levels.…”
Section: Discussionsupporting
confidence: 54%
“…Only 20 % of this was in an ALextractable form (and hence reactive in short-term laboratory experiments). This result can be compared to the study of Börling et al (2004), who reported results for Kungsängen and for eight other Swedish soil fertility experiments with similar P fertilization levels.…”
Section: Discussionsupporting
confidence: 54%
“…Olsen P was divided by PSI to get an estimate of the DPS (e.g., Westermann et al, 2001;Börling et al, 2004):…”
Section: Soil Sampling and Analysesmentioning
confidence: 99%
“…Em consequência, vários estudos já foram desenvolvidos sobre perdas de nutrientes na agricultura via escoamento superficial (Favaretto et al, 2006;Sharpley et al, 2001), inclusive no Brasil (Bertol et al, 2003Peles, 2007;Mori, 2008). Com relação à qualidade da água subterrânea associada a práticas agrícolas, ênfase vinha sendo dada ao N (Smith et al, 1990;Owens, 1994;White et al, 1998;Bakhsh et al, 2005;Basso et al, 2005;Bertol et al, 2005;Garg et al, 2005); no entanto, nos últimos anos tem se discutido também o transporte de P em subsuperfície Favaretto, 2002;Börling et al, 2004;Basso et al, 2005;Bertol, 2005;Fortune et al, 2005).…”
Section: Introductionunclassified